2022
DOI: 10.1109/access.2022.3144390
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence, Algorithmic Competition and Market Structures

Abstract: The use of artificial intelligence (AI) in the form of pricing algorithms to increase profits is becoming ubiquitous. However, the literature has focused on specific markets and algorithms so far, but it is unclear what happens across algorithms and markets. To analyze the business and economic impact of pricing algorithms, we build a computational model that considers two sophisticated AI algorithms (Q-learning and Particle Swarm Optimization) competing in prices in three different market structures (Logit, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 31 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…The details of the agent-based computational model are presented next. Other researchers have used agentbased computational modeling to study technological innovation, market dynamics, and other economic problems [39][40][41][42][43][44].…”
Section: Methodsmentioning
confidence: 99%
“…The details of the agent-based computational model are presented next. Other researchers have used agentbased computational modeling to study technological innovation, market dynamics, and other economic problems [39][40][41][42][43][44].…”
Section: Methodsmentioning
confidence: 99%
“…Producers know the production cost of a good better than consumers (excluding externalities associated with production). However, algorithms are increasingly capable of differentiating prices depending on moment and place, so 'objective' price information is harder to get (Calvano et al, 2020;Sanchez-cartas, 2022).…”
Section: Market Economics: An Increasing Divergence Between Model And...mentioning
confidence: 99%
“…For example, auctions have become a popular tool for price discovery and trade gain optimization, highlighting the crucial role that market design plays in these processes. Early studies, beginning with Vickrey in 1961, demonstrated that careful planning is required in auctions and other market institutions in order to produce effective results [1].…”
Section: Introductionmentioning
confidence: 99%